Gun culture or gun control : firearms, violence and society - Squires, Peter, 1958- (Routledge, 2000)
This book presents the first substantial analysis of the social and political reactions to events such as the Dunblane disaster in 1996 and also examines many of the wider issues relating to gun control in the United Kingdom.